A complex biostimulant based on plant flavonoids enhances potato growth and commercial yields - Salvage, Richard; Cannon, Tim; Kingsmill, Philip; Liu, Fuquan; Fleming, Colin C. (Frontiers in Sustainable Food Systems, 2024)
Introduction Potatoes are one of the world’s most important agricultural crops, with potential for making a major contribution to global food security. This study shows how a biostimulant derived from a plant extract can improve potato crop yield and global food supply. Successful potato production currently requires significant levels of inputs including fertiliser, pesticides and irrigation, however non-microbial plant biostimulants or mixtures of biostimulants with synergistic actions, have the capacity to reduce inputs and improve the sustainability of intensive agriculture. Methods A complex biostimulant containing a number of flavonoids including protocatechuic acid, quercetin, chlorogenic acid, coumaroyl quinic acid and gentistic acid was tested against three potato varieties for its efficacy in improving plant growth characteristics and tuber production in controlled and field environments. Results In containers, complex biostimulant treatment enhanced photosynthetic ability, with elevated levels of chlorophyll, higher specific leaf areas and significantly larger leaf assimilation areas. Treatment also significantly increased tuber yield by an average of 33% in tuber weight across three potato varieties and shifted tuber production toward larger sized tubers. The biostimulant derived from flavonoids was also assessed in 6 commercial potato crops and consistently increased total yield (average 5.2%) and marketable yield, representing an increase in margins of UK£700 per hectare across the 6 crops. Similar increases in yield were seen when comparing chitted and unchitted seed potatoes and both types of seed responded positively to biostimulant application. Biostimulant treatment had no significant effects on tuber specific gravity, dry matter percentage and starch content, except at one location where these quality characteristics were higher in the control plants. Conclusion The flavonoid based complex biostimulant produced significant effects on potato yield and quality in both container experiments and in field trials indicating its potential for contributing to sustainable potato production.